The AARTFAAC Cosmic Explorer: observations of the 21-cm power spectrum in the EDGES absorption trough. Issue 3 (9th October 2020) - Gehlot, B K; Mertens, F G; Koopmans, L V E; Offringa, A R; Shulevski, A; Mevius, M; Brentjens, M A; Kuiack, M; Pandey, V N; Rowlinson, A; Sardarabadi, A M; Vedantham, H K; et al.
ABSTRACT: The 21-cm absorption feature reported by the EDGES collaboration is several times stronger than that predicted by traditional astrophysical models. If genuine, a deeper absorption may lead to stronger fluctuations on the 21-cm signal on degree scales (up to 1 K in rms), allowing these fluctuations to be detectable in nearly 50 times shorter integration times compared to previous predictions. We commenced the 'AARTFAAC Cosmic Explorer' (ACE) program, which employs the AARTFAAC wide-field image, to measure or set limits on the power spectrum of the 21-cm fluctuations in the redshift range z = 17.9–18.6 (Δ ν = 72.36–75.09 MHz) corresponding to the deep part of the EDGES absorption feature. Here, we present first results from two LST bins: 23.5–23.75 and 23.75–24.00 h, each with 2 h of data, recorded in 'semi drift-scan' mode. We demonstrate the application of the new ACE data-processing pipeline (adapted from the LOFAR-EoR pipeline) on the AARTFAAC data. We observe that noise estimates from the channel and time-differenced Stokes V visibilities agree with each other. After 2 h of integration and subtraction of bright foregrounds, we obtain 2 σ upper limits on the 21-cm power spectrum of $Δ _{21}^2 \lt (8139~mK)^2$ and $Δ _{21}^2 \lt (8549~mK)^2$ at $k = 0.144~h\, cMpc^{-1}$ for the two LST bins. Incoherently averaging the noise bias-corrected power spectra for the two LST bins yields an upper limit of $Δ _{21}^2 \lt (7388~mK)^2$ at $k = 0.144~h\, cMpc^{-1}$ . These are the deepest upper limits thus far at these redshifts.